Fulfillment of Expectations after Orthopaedic Foot and Ankle Surgery: An Analysis of 271 Patients with 2-year Follow-up. Issue 4 (16th October 2019) - Henry, Jensen K.; Roney, Andrew; Hummel, Amelia; Cody, Elizabeth; Ellis, Scott
Category: Ankle, Ankle Arthritis, Arthroscopy, Bunion, Hindfoot, Lesser Toes, Midfoot/Forefoot, Sports, General Foot/Ankle, Outcomes, Satisfaction Introduction/Purpose: Success in orthopaedic surgery was traditionally defined by postoperative radiographs or legacy outcomes scores, but increasingly incorporates more patient-centered metrics. Patient expectations are one such measure, and have been described using a new validated survey for foot/ankle patients. Understanding patients' expectations of surgery is critical in order to facilitate shared decision-making and set reasonable goals for outcomes. In other specialties, postoperative expectations surveys have also been created and shown to correlate with measures of satisfaction and traditional patient-reported outcomes scores. However, there are no such studies in the foot and ankle literature. This study aimed to validate a method of assessing expectation fulfillment in foot/ankle patients postoperatively. We hypothesized that the survey would significantly correlate with measures of improvement, satisfaction, and clinical outcomes scores. Methods: This is a single-center prospective study of patients undergoing elective foot and ankle procedures. Preoperative demographics, clinical data, and Foot & Ankle Outcomes Score (FAOS) were collected. Patients completed the expectations survey, consisting of 23 questions for domains including pain, ambulation, daily functioning, exercise/sports, shoe wear, and generalized items like "improving confidence in foot/ankle" and "going back to normal." Postoperatively, patients answered how much improvement they received for each item listed on the preoperative survey. Using previously validated methods, the proportion of expectations fulfilled was calculated as a ratio of the preoperative to postoperative expectations score, with values of 0 -1 indicating some expectations met, 1 indicating expectations met; and >1 indicating expectations surpassed. Receiver operator characteristic (ROC) curves and areas under the curve (AUC) with 95% confidence intervals (CI) were used to compare the expectations survey to other outcomes scales, including FAOS, perceived improvement, overall fulfillment, Delighted-Terrible scale, and satisfaction. Results: 271/340 (80%) of patients with preoperative data completed 2-year follow-up (mean age 55.4 years, mean BMI 27.5, 65% female). Most common diagnoses were hallux valgus (25%), flatfoot (11%), hallux rigidus (11%), and ankle arthritis (10%). Mean proportion of expectations fulfilled was 1.15, indicating surpassed expectations. The proportion of expectations fulfilled correlated best with perceived improvement, global expectation fulfillment, and the Delighted-Terrible scale, and to a lesser degree with satisfaction and change in FAOS (all except activity). Based on the inflection point of the ROC curves corresponding to greatest AUC (Table), a clinically important proportion of expectations fulfilled was 0.81 and correlated with feeling delighted (sensitivity 0.88, specificity 0.85), improvement (sensitivity 0.89, specificity 0.83), overall expectations (sensitivity 0.91, specificity 0.81), and satisfaction (sensitivity 0.85, specificity 0.81). Conclusion: The proportion of expectations fulfilled is a valid outcome tool for foot and ankle surgery. It is uniquely able to capture pre- and postoperative data in one value and can be tailored to each patient's specific goals. This survey can be used by surgeons after a variety of procedures to assess if a patient's specific expectations have been fulfilled after surgery. We can use this tool to assess which patient and surgical factors may influence the fulfillment of expectations. This, in turn, will help surgeons better indicate the appropriate procedure in the optimal patient to achieve the greatest postoperative success.